Desenvolvimento sustentável e turismo : um estudo sobre as políticas de turismo implementadas pelo Governo do Estado de Roraima no período de 1992 a 2017 - Macedo, Brenda Maribel Pinedo (2018)
Globally, tourism is a complex and intersectoral economic activity that is on the rise and can be an instrument for sustainable local development. Due to the social and environmental complexity which surrounds the area of tourism, policies for its organization are indispensable. In this context, this work aims to show actions in tourism carried out by the Government of the State of Roraima between 1992 and 2017. It is a theoretical-analytical study, with a qualitative approach and utilizes bibliographic and documental research. Through theoretical references the study analyzes the development of tourism and its impacts with the participation of the State. Through document analysis, it links the main public policies of tourism in Brazil and the actions, plans and programs, planned and executed, by the government of Roraima for the sustainable development of tourism. The results show the difficulties faced by the state government in achieving its objectives and goals related to the development of a tourism policy that meets local needs, although there exist, nationally, federal government programs aimed at the development of tourism in the regions of the country. The principal reason for this is the lack of a more qualified technical staff to promote tourism in the State bureaucracy.